2022
DOI: 10.3389/fmolb.2022.1096679
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value, immune signature and molecular mechanisms of the SUMO family in pancreatic adenocarcinoma

Abstract: Background: Pancreatic adenocarcinoma (PAAD) has a high degree of malignancy and a very poor prognosis, and the 5-year overall survival rate of patients is approximately 7%. To improve the prognosis of patients with PAAD, a more comprehensive and in-depth study of the pathogenesis of PAAD and the identification of new diagnostic markers and treatment targets are urgently needed. Increasing evidence supports that the small ubiquitin-like modifier (SUMO) family is closely related to the occurrence and developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…While SUMO-1 decreases autophagy [148,149], it also significantly increases hypoxic cell stress [150], and induces the expression of Ras-related C3 botulinum toxin substrate 1 (RAC1) [149]. Collectively, this leads to microtubule polymerization and integrin clustering that will progress to lung cancer [151,152], glioblastoma [153], endometrial cancer [154], actinic cheilitis and lip carcinoma [155], liver cancer [156,157], gastric cancer [158] or pancreatic carcinoma [159]. SUMOylation is used by viruses to modify their own proteins [160,161], most notably by HPV [162], cytomegalovirus (CMV) [163) or Epstein-Barr virus (EBV) [164,165] to support their own replication.…”
Section: Molecular Mechanisms Underlying Emt and Metmentioning
confidence: 99%
“…While SUMO-1 decreases autophagy [148,149], it also significantly increases hypoxic cell stress [150], and induces the expression of Ras-related C3 botulinum toxin substrate 1 (RAC1) [149]. Collectively, this leads to microtubule polymerization and integrin clustering that will progress to lung cancer [151,152], glioblastoma [153], endometrial cancer [154], actinic cheilitis and lip carcinoma [155], liver cancer [156,157], gastric cancer [158] or pancreatic carcinoma [159]. SUMOylation is used by viruses to modify their own proteins [160,161], most notably by HPV [162], cytomegalovirus (CMV) [163) or Epstein-Barr virus (EBV) [164,165] to support their own replication.…”
Section: Molecular Mechanisms Underlying Emt and Metmentioning
confidence: 99%
“…Altered expression or mutations in these proteins can influence gene regulation and potentially contribute to tumor development (Seeler et al., 1998; Yordy et al., 2004). A previous study demonstrated a significant association between high SP family member expression in pancreatic adenocarcinoma (PAAD) and unfavorable clinicopathological characteristics as well as a poor prognosis for patients with PAAD (Duan et al., 2023). SP110 and SP140 showed high rates of nonsynonymous mutations in head and neck squamous cell carcinoma (Chang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%